New Things in the Catholic Interpretation of Science - Garadža, Vitalijus (Problemos, 1970)
Though the Second Vatican Council showed the strivings of the church for adapting itself to modern reality, the traditional neo-Thomist conception of science, based on the teaching of harmony existing between faith and reason and having found its official expresion in the papal encyclic “Humani generis” (1950), remained valid. New things without changing the essence of this conception come to more realistic evaluation of scientific achievements in reality cognition and the role of science in the life of society. By acknowledging the increasing role of science in cognition and reconstruction of the world the church attempts, as before, to subdue science to religion. Neo-Thomists absolutize historical limitedness of scientific knowledge basing the necessity of appealing to religious faith in search for the very profound truth and genuine values, which disregarding science becomes a menace to man and society. Though forced to retreat against the onset of science Catholicism remains a factor invariably hostile to science: the assertion of religion is based on the depreciation of cognitive possibilities of science and on the distortion of its social function.